2006
DOI: 10.1172/jci27341
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in neuronal TGF-β signaling promotes neurodegeneration and Alzheimer’s pathology

Abstract: Alzheimer's disease (AD) is characterized by progressive neurodegeneration and cerebral accumulation of the β-amyloid peptide (Aβ), but it is unknown what makes neurons susceptible to degeneration. We report that the TGF-β type II receptor (TβRII) is mainly expressed by neurons, and that TβRII levels are reduced in human AD brain and correlate with pathological hallmarks of the disease. Reducing neuronal TGF-β signaling in mice resulted in age-dependent neurodegeneration and promoted Aβ accumulation and dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
248
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(257 citation statements)
references
References 63 publications
9
248
0
Order By: Relevance
“…34 At the opposite, a deficiency in neuronal TGF-b signalling was reported to promote neurodegeneration and Alzheimer's pathology. 33 Interestingly, HtrA1 was also directly involved in the b-amyloid pathway, in which HtrA1 colocalizes with b-amyloid deposits in human brain samples and reduces Ab accumulation in astrocytes cell culture supernatants. 15 In parallel, we have previously demonstrated that TGF-b treatment in both murine and human cultured astrocytes leads to an increased transcription of APP and subsequent accumulation of Ab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 At the opposite, a deficiency in neuronal TGF-b signalling was reported to promote neurodegeneration and Alzheimer's pathology. 33 Interestingly, HtrA1 was also directly involved in the b-amyloid pathway, in which HtrA1 colocalizes with b-amyloid deposits in human brain samples and reduces Ab accumulation in astrocytes cell culture supernatants. 15 In parallel, we have previously demonstrated that TGF-b treatment in both murine and human cultured astrocytes leads to an increased transcription of APP and subsequent accumulation of Ab.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similarly, although it has been proposed that AD is accompanied by increased TGF-b levels within the brain parenchyma, 31 a recent report suggests that TGF-b signalling might be downregulated due to a reduced expression of its TbR-II receptor. 33 Similarly, conflicting data have been published regarding the potential role of altered TGF-b levels in AD. For instance, in human amyloid precursor protein (hAPP) transgenic mice, a moderate increase in astrocytic expression of TGF-b1 was proposed to lead to a reduced Ab accumulation because of a TGF-b-dependent phagocytosis of Ab by microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TGF-b1 is enriched in plasma lipoprotein samples of apoliprotein E3 (apoE3), but occurs at a lower concentration in lipoproteins containing apoE4, a genetic risk factor for late-onset Alzheimer's disease (Tesseur et al 2009;Bertram et al 2010). Impairment in TGF-b/Smad signaling and decreased neuronal expression of TbRII are both characteristics of disease pathology, providing further evidence for a role for TGF-b in Alzheimer's disease (Tesseur et al 2006;Ueberham et al 2006;Wang et al 2010).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…TGF-b signaling has been reported to be insufficient in the brains of AD patients [123]. This deficiency has been shown to cause more Ab deposition and neurodegeneration [123], while treatment with TGF-b prevents Ab-induced neurotoxicity [124].…”
Section: Tgfb1mentioning
confidence: 99%